Converting the Story: Toward a Theory of Narrative Conversion in the Muslim Tale of Ǧirǧīs (St. George) - R. Brian Siebeking (Al-Qantara : Revista de Estudios Arabes, 2024)
When analyzing literary works that cross religious and cultural boundaries, scholars often reach for the language of appropriation. This framework takes stories as raw materials, to be mined, reshaped, and redeployed as the redactor sees fit. But is a story a wholly passive body? And if not, is there an analytical frame more helpful in drawing out its activity? With these queries in mind, I propose the following study: What would happen if we approached the boundary-crossing editorial process as a type of conversion, and the story itself as a convert? For this experiment, I take up the Islamized Tale of Ǧirǧīs (St. George) as a case study, using it to support some preliminary remarks on a theory of narrative conversion. Reading this homiletic story against the stages of conversion proposed by Lewis R. Rambo, I argue for the heuristic utility of conversion as a framework for revealing the subtle ways that stories are active in their own transformation. Ultimately, I advocate for the adoption of this new frame as a basis for further theorizing about why and how stories transmigrate from one religious or cultural world to another.